2020
DOI: 10.1093/mnras/staa088
|View full text |Cite
|
Sign up to set email alerts
|

Arm–interarm gas abundance variations explored with MUSE: the role of spiral structure in the chemical enrichment of galaxies

Abstract: Spiral arms are the most characteristic features of disc galaxies, easily distinguishable due to their association with ongoing star formation. However, the role of spiral structure in the chemical evolution of galaxies is unclear. Here we explore gas-phase abundance variations between arm and interarm regions for a sample of 45 spiral galaxies using high spatial resolution VLT/MUSE Integral Field Spectroscopy data. We report the presence of more metal-rich H ii regions in the spiral arms with respect to the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 94 publications
3
18
0
Order By: Relevance
“…Preliminary results from the first eight completed galaxies in the PHANGS-MUSE survey (Kreckel et al 2019, hereafter Paper I) reveal that half exhibit significant azimuthal variations, and suggest that spiral arms play a role in organizing and mixing the ISM. These statistics have been recently confirmed with a larger sample of 45 disc galaxies (Sánchez-Menguiano et al 2020).…”
supporting
confidence: 55%
“…Preliminary results from the first eight completed galaxies in the PHANGS-MUSE survey (Kreckel et al 2019, hereafter Paper I) reveal that half exhibit significant azimuthal variations, and suggest that spiral arms play a role in organizing and mixing the ISM. These statistics have been recently confirmed with a larger sample of 45 disc galaxies (Sánchez-Menguiano et al 2020).…”
supporting
confidence: 55%
“…However, they found that gas elements quickly exchange abundances after migrating, leading to small azimuthal dispersions in abundance. Sánchez-Menguiano et al (2020) found that azimuthal variations in abundances are stronger in galaxies with stronger bars and grand-design spirals, which supports non-axisymmetric structure driving azimuthal inhomogeneities.…”
Section: Introductionmentioning
confidence: 66%
“…Pilyugin et al 2014;Sánchez-Menguiano et al 2016;Belfiore et al 2017;Poetrodjojo et al 2018). Furthermore, some observations show azimuthal variations (Sánchez et al 2015;Vogt et al 2017;Ho et al 2017Ho et al , 2018Kreckel et al 2019;Kreckel et al 2020;Sánchez-Menguiano et al 2020), while others show no azimuthal variations within measurement uncertainty ( 0.05 dex) (e.g. Cedrés & Cepa 2002;Zinchenko et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Erroz-Ferrer et al 2019;Sánchez-Menguiano et al 2019;Wang & Lilly 2021), or the presence of spiral arms (e.g. Ho et al 2017;Sánchez-Menguiano et al 2020). In this study we will consider the process mean to depend solely on the metallicity gradient, as described in Equation 3.…”
Section: Hierarchical Models Of Spatial Structurementioning
confidence: 99%